One new species of Amphinemura and description of the female of A. ancistroidea Li & Yang (Plecoptera: Nemouridae) from Guangxi Zhuang Autonomous Region of southern China - Mo, Raorao; Yang, Ding; Wang, Guoquan; Li, Weihai (Zootaxa, 2017)
A new nemourid species, Amphinemura yao sp. nov. is described from the Daoyao Mountains of Guangxi Zhuang Autonomous Region of southern China. Amphinemura ancistroidea Li & Yang, 2007 is newly recorded from Guangxi and the female is described for the first time including the internal vaginal complex. The new species is compared with related taxa.